STRENGTH PREDICTION AND OPTIMIZATION OF ANIMAL BONE ASH- METAKAOLIN CEMENT BLENDS VIA RESPONSE SURFACE METHODOLOGY (Journal of Pure and Applied Sciences (Science Forum), 2025)
This paper tries to investigate the effect of blending animal bone ash (ABA) andmetakaolin (MK) on the mortar compressive strength of ternary cement blends. Themortar strengths of the ternary cement blends are influenced by several parameterssuch as blending ratio, replacement level and curing age. The mortar strength ofthe ternary cement blend was optimized via response surface methodology usingcentral composite design and Box and Behnken design. Both models were comparedto obtain the best strength prediction. Results showed that both modelsexperimental data for the prediction of the mortar strength satisfied second orderpolynomial regression. The mortar strength of ABA-MK-PLC experienced an increaseas the blending ratio between 0.2 -0.5 and curing age between 3 -60 days whereasa slight reduction in the mortar strength was observed as the replacement level wasincreased between 7.5 – 12.5 wt.%. This slight diminution observed despite the highreplacement level further proves that pozzolanic activities occurred. The analysis ofvariance (ANOVA) indicated that the curing age significantly affected the responsefor both CCD and BBD models respectively with the best mortar strength predictionvia CCD. The ANOVA revealed that predicted R2 (R2pred) and R2 for CCD was very closein comparison with BBD and thus most suitable to describe the mortar compressivestrength of the cement blends with R2pred of 0.9107. The interactive effect of theblending ratio, replacement level and curing age were also investigated andoptimized. The optimum condition for the prediction of the mortar strength of theternary cement blend were blending ratio 0.423, replacement level 7.565 wt.%, andcuring age 60 days.